Microstructural evidence of the toughening mechanisms of polyurethane reinforced with halloysite nanotubes under high strain-rate tensile loading - Rafaela Aguiar (Nature Portfolio, 2021)
Abstract In this study, we have investigated the relationship between the spherulitic morphology and the dynamic tensile response of polyurethane reinforced with Halloysite nanotubes (HNTs). The polyurethane prepolymer is partially silane end-capped and filled with only 0.8 wt.% of acid-treated Halloysite nanotubes. The resultant nanocomposite material presents a 35% higher spall strength compared to the neat polyurethane and 21% higher fracture toughness. We show evidence that the HNTs are not the toughening phase in the nanocomposite, but rather it is their influence on the resultant spherulitic structures which alters the polymer microstructure and leads to a tougher dynamic response. Microstructural characterization is performed via Scanning Electron Microscopy, Atomic Force Microscopy and Field Emission Scanning Electron Microscopy, and crystallinity examination via X-ray diffraction. The spherulitic structures present a brittle fracture character, while the interspherulitic regions are more ductile and show large deformation. The nanocomposite presents a finer and more rigid spherulitic structure, and a more energy dissipative fracture mechanism characterized by a rougher fracture surface with highly deformed interspherulitic regions.